2022
DOI: 10.1186/s12879-022-07861-x
|View full text |Cite
|
Sign up to set email alerts
|

Bedaquiline safety, efficacy, utilization and emergence of resistance following treatment of multidrug-resistant tuberculosis patients in South Africa: a retrospective cohort analysis

Abstract: Background This retrospective cohort study assessed benefits and risks of bedaquiline treatment in multidrug-resistant-tuberculosis (MDR-TB) combination therapy by evaluating safety, effectiveness, drug utilization and emergence of resistance to bedaquiline. Methods Data were extracted from a register of South African drug-resistant-tuberculosis (DR-TB) patients (Electronic DR-TB Register [EDRWeb]) for newly diagnosed patients with MDR-TB (includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(38 reference statements)
0
6
1
Order By: Relevance
“…Large national or subnational molecular epidemiology studies have quantified population-level bedaquiline resistance, 14 , 29 and one study found an overall baseline bedaquiline resistance rate of 5·0% (19 of 383) in people with drug-resistant tuberculosis in South Africa, with 3·5% (five of 142) of people gaining resistance in the longitudinal cohort. 30 This difference in the magnitude of resistance gain versus our study is possibly attributable to patient profiles (all patients starting bedaquiline in these other studies vs patients with complex treatment histories and sustained culture positivity in our study). We did not quantify bedaquiline minimal inhibitory concentrations, as our objective was to characterise the proportion of people whose minimal inhibitory concentrations exceeded the critical concentration for bedaquiline; however, our isolates will contribute to future efforts to accomplish this important goal.…”
Section: Discussioncontrasting
confidence: 63%
“…Large national or subnational molecular epidemiology studies have quantified population-level bedaquiline resistance, 14 , 29 and one study found an overall baseline bedaquiline resistance rate of 5·0% (19 of 383) in people with drug-resistant tuberculosis in South Africa, with 3·5% (five of 142) of people gaining resistance in the longitudinal cohort. 30 This difference in the magnitude of resistance gain versus our study is possibly attributable to patient profiles (all patients starting bedaquiline in these other studies vs patients with complex treatment histories and sustained culture positivity in our study). We did not quantify bedaquiline minimal inhibitory concentrations, as our objective was to characterise the proportion of people whose minimal inhibitory concentrations exceeded the critical concentration for bedaquiline; however, our isolates will contribute to future efforts to accomplish this important goal.…”
Section: Discussioncontrasting
confidence: 63%
“…In addition, we note that the rate of loss to followup was higher in this registry than elsewhere [22]. Results from a much larger (> patients) retrospective South African registry [28] showed increased rates of treatment success and reduced mortality in patients receiving bedaquiline.…”
Section: Discussionmentioning
confidence: 58%
“…Among the latter, 60% had an adverse treatment outcome. The majority of the cohort were HIV positive and all but one of those with emergent resistance had preexisting additional resistance to fluoroquinolones and/or aminoglycosides [13 ▪ ].…”
Section: All-oral Multidrug Resistant Tuberculosis Treatment Regimens...mentioning
confidence: 99%